2013
DOI: 10.1016/j.applanim.2012.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Stress, the HPA axis, and nonhuman primate well-being: A review

Abstract: Numerous stressors are routinely encountered by wild-living primates (e.g., food scarcity, predation, aggressive interactions, and parasitism). Although many of these stressors are eliminated in laboratory environments, other stressors may be present in that access to space and social partners is often restricted. Stress affects many physiological systems including the hypothalamic-pituitary-adrenocortical (HPA) axis, which is the focus of this review. The glucocorticoid, cortisol, is the ultimate output of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
113
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(119 citation statements)
references
References 120 publications
3
113
0
3
Order By: Relevance
“…This is in line with the incidence rate of HZ in bone marrow transplant patients, which had been reported to reach 43%(Chen et al , 2014; Koc et al , 2000; Novak et al , 2013). However, our reactivation rates are lower than those observed in macaques that have undergone whole body irradiation coupled with immune suppressive treatments (Mahalingam et al , 2010), in line with the reduced severity of immune suppression due to accelerated senescence of only one T cell compartment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is in line with the incidence rate of HZ in bone marrow transplant patients, which had been reported to reach 43%(Chen et al , 2014; Koc et al , 2000; Novak et al , 2013). However, our reactivation rates are lower than those observed in macaques that have undergone whole body irradiation coupled with immune suppressive treatments (Mahalingam et al , 2010), in line with the reduced severity of immune suppression due to accelerated senescence of only one T cell compartment.…”
Section: Discussionsupporting
confidence: 88%
“…Also, fecal cortisol increases have also been observed in chimpanzees moved to a new facility (Reimers et al, 2007). In addition, temporary moves of two days or less have also been shown to increase cortisol levels in rhesus, bonnet and cynomolgus macaques as well (Novak et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, steroids measurement in hair allows a long-term evaluation of chronic stress with a negligible influence of acute stress events (Novak et al, 2013). Hair sampling is a non-invasive, easy and painless procedure and has a low level of invasiveness associated with the sample collection.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has since been applied in studies of chronic HPA axis activity (i.e., accumulation of cortisol into the hair shaft over the past several months, as opposed to minutes or hours as in the point samples mentioned above) in both animals (Bechchøft et al, 2012; Davenport et al, 2008; Malcom et al, 2012; Meyer and Novak, 2012; Novak et al, 2013) and humans (O’Brien et al, 2012; Vanaelst et al, 2013). Studies utilizing hair cortisol have shown that HCCs decline during the first several years of life in several nonhuman primate species including rhesus monkeys (Dettmer et al, 2012; Feng et al, 2011), vervets (Laudenslager et al, 2012), and baboons (Fourie & Bernstein, 2011), and one study also demonstrated sex differences in HCCs in nonhuman primates during puberty and adulthood (Laudenslager et al, 2012).…”
Section: Introductionmentioning
confidence: 99%